Pathophysiologic and clinical implications of molecular profiles resultant from deletion 5q - Vera Adema; Laura Palomo; Wencke Walter; Mar Mallo; Stephan Hutter; Thomas La Framboise; Leonor Arenillas; Manja Meggendorfer; Tomas Radivoyevitch; Blanca Xicoy; Andrea Pellagatti; Claudia Haferlach; et al. (EBioMedicine, 2022)
Summary: Background: Haploinsufficiency (HI) resulting from deletion of the long arm of chromosome 5 [del(5q)] and the accompanied loss of heterozygosity are likely key pathogenic factors in del(5q) myeloid neoplasia (MN) although the consequences of del(5q) have not been yet clarified. Methods: Here, we explored mutations, gene expression and clinical phenotypes of 388 del(5q) vs. 841 diploid cases with MN [82% myelodysplastic syndromes (MDS)]. Findings: Del(5q) resulted as founder (better prognosis) or secondary hit (preceded by TP53 mutations). Using Bayesian prediction analyses on 57 HI marker genes we established the minimal del(5q) gene signature that distinguishes del(5q) from diploid cases. Clusters of diploid cases mimicking the del(5q) signature support the overall importance of del(5q) genes in the pathogenesis of MDS in general. Sub-clusters within del(5q) patients pointed towards the inherent intrapatient heterogeneity of HI genes. Interpretation: The underlying clonal expansion drive results from a balance between the “HI-driver” genes (e.g., CSNK1A1, CTNNA1, TCERG1) and the proapoptotic “HI-anti-drivers” (e.g., RPS14, PURA, SIL1). The residual essential clonal expansion drive allows for selection of accelerator mutations such as TP53 (denominating poor) and CSNK1A1 mutations (with a better prognosis) which overcome pro-apoptotic genes (e.g., p21, BAD, BAX), resulting in a clonal expansion. In summary, we describe the complete picture of del(5q) MN identifying the crucial genes, gene clusters and clonal hierarchy dictating the clinical course of del(5q) patients. Funding: Torsten Haferlach Leukemia Diagnostics Foundation. US National Institute of Health (NIH) grants R35 HL135795, R01HL123904, R01 HL118281, R01 HL128425, R01 HL132071, and a grant from Edward P. Evans Foundation.